Building TabuCount Application to counting Tabu Search iteration with Borland Delphi 7 - ., Miswanto; Yudha, Bramantara; ., Sapriyanti; Setiawan, Hendra; Novel, Kadinar (International Journal of Engineering and Technology, 2018)
This research aims to build desktop application called TabuCount with Borland Delphi 7.0 application in the Software Engineering subject. TabuCount helping other researchers or other students who used Tabu Search Algorithm like Travelling Salesman Problem to count each iteration step by step, and minimized human error for counting number. This research used Research and Development (R&D) design procedures through 5 steps, which are: (1) data classification, (2) data collecting, (3) design application, (4) field testing, and (5) building application. Based on the results of manual count with Ms. Excel and the TabuCount result, it was obtained the same result are valid and applicable. For an effective based on the research, TabuCount application were effective to use. Therefore, researchers who wanted to use Tabu Search Algorithm (Travel Salesman Problem) is suggested to use TabuCount as an alternative support application.Â Â